Surface dielectric functions of a free-electron gas - Miraglia, Jorge Esteban (2002)
We investigate the surface dielectric response of a free-electron gas to a projectile moving parallel to the surface. Three theoretical models are examined, viz., the specular reflection and the parallel dispersion models, and a here-proposed axial model. The mean-free path, the stopping, the straggling, and the self-induced potential at the projectile position, are calculated in terms of the distance of the projectile to the surface. Differences at level of energy-loss distribution are found. We conclude that the axial model is reliable, has a simple closed form and permits us to estimate the binary contribution.